2002
DOI: 10.1007/s11926-002-0081-2
|View full text |Cite
|
Sign up to set email alerts
|

The relation between antiphospholipid syndrome-related pregnancy morbidity and non-gravid vascular thrombosis: A review of the literature and management strategies

Abstract: The antiphospholipid syndrome (APS) is associated with pregnancy morbidity and vascular thrombosis in the presence of circulating antiphospholipid (aPL) antibodies. Clinical manifestations of aPL antibodies represent a spectrum (asymptomatic, pregnancy events, vascular events, or both pregnancy and vascular events), and APS should not be considered a single disease with a predictable outcome. Patients with aPL antibodies are at increased risk of vascular thrombotic events during pregnancy, the postpartum perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 37 publications
0
7
0
2
Order By: Relevance
“…Although management of aPL-positive patients is controversial because of limited well-designed controlled trials, several points need to be emphasized [14]: (1) corticosteroids are not indicated in the management of Sapporo APS classification criteria Clinical criteria 1. Vascular thrombosis One or more clinical episodes of arterial, venous, or small vessel thrombosis in any tissue or organ 2.…”
Section: Clinical Discussion: Rheumatologicmentioning
confidence: 99%
“…Although management of aPL-positive patients is controversial because of limited well-designed controlled trials, several points need to be emphasized [14]: (1) corticosteroids are not indicated in the management of Sapporo APS classification criteria Clinical criteria 1. Vascular thrombosis One or more clinical episodes of arterial, venous, or small vessel thrombosis in any tissue or organ 2.…”
Section: Clinical Discussion: Rheumatologicmentioning
confidence: 99%
“…Therefore, it is desirable to continue LMWH during labor or delivery in women receiving antenatal thromboprophylaxis (21) . The duration of recommendations range from 3-5 days (21) , to 6-8 weeks (76) and up to 12 weeks (77) .…”
Section: Therapeutic Optionsmentioning
confidence: 99%
“…anticardiolipin, lupus anticoagulant) which may be associated with spontaneous fetal loss of 50-75%, hypertensive syndromes indistinguishable from pre-eclampsia and thrombotic events including deep vein thrombosis, pulmonary embolus, myocardial infarction and strokes. 32 Thus all women with systemic lupus erythematosus should be screened for antiphospholipid antibodies prior to pregnancy or early in gestation. When titres are elevated (more than 40 GPL), daily aspirin (80 -325 mg) is recommended and low molecular weight heparin is generally prescribed.…”
Section: Lupus Nephritismentioning
confidence: 99%